2007
DOI: 10.1108/13639510710753243
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COMPSTAT on reported crime in Queensland

Abstract: Purpose -The purpose of this paper is to evaluate the impact of Queensland Police Service's version of COMPSTAT, known as "Operational Performance Reviews" (OPRs), on reported crime. Design/methodology/approach -The paper employed interrupted time series analytic techniques to examine the impact of OPRs on various categories of reported crime in Queensland. The analyses assessed the extent to which OPRs were associated with crime reductions across the 29 police districts in Queensland. Findings -The introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…A negative, significant Time-OPR interaction (p b .05) indicates that, compared to pre-OPR, the monthly post-OPR log rate of unlawful entry into other types of premises is decreased by, on average, 0.004. Most of this decline can be attributable to the efforts of two police districts (see Mazerolle et al, 2007b). The overall result is consistent with previously-attained results of other timeseries analyses (Mazerolle, Rombouts, et al, 2007a, 2007b; see also Chilvers & Weatherburn, 2004) and highlights the substantial contributory role of post-OPR reductions in unlawful entry have on overall state crime trends.…”
Section: Unarmed Robberysupporting
confidence: 85%
See 2 more Smart Citations
“…A negative, significant Time-OPR interaction (p b .05) indicates that, compared to pre-OPR, the monthly post-OPR log rate of unlawful entry into other types of premises is decreased by, on average, 0.004. Most of this decline can be attributable to the efforts of two police districts (see Mazerolle et al, 2007b). The overall result is consistent with previously-attained results of other timeseries analyses (Mazerolle, Rombouts, et al, 2007a, 2007b; see also Chilvers & Weatherburn, 2004) and highlights the substantial contributory role of post-OPR reductions in unlawful entry have on overall state crime trends.…”
Section: Unarmed Robberysupporting
confidence: 85%
“…Prior research conducted in Queensland found that implementation of Operational Performance Reviews (OPRs), akin to COMPSTAT in the US, resulted in state-wide reductions in different categories of crime (see Mazerolle, Rombouts, et al, 2007a, 2007b. The first aim of the present research was to contextualize these overall findings by exploring differences between 29 police districts in the state of Queensland.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 87%
See 1 more Smart Citation
“…That strategy was associated with marked decreases in community crime statistics at the time (late 1990s). Since then, it has been applied in many locations, including the Australian Capital Territory, New South Wales and Queensland (Ratcliffe 2008, Mazerolle & Rombouts 2007. To date, the main application appears to have been used in localised community policing.…”
Section: Mappingmentioning
confidence: 99%
“…Commentary by various scholars (Eterno & Silverman, 2006;Firman, 2003;Kania, 2004;Klinger, 2003;Magers, 2004;McDonald, 2000;Moore, 2003;Moore & Braga, 2003;Silverman, 2006;Vito, Walsh, & Kunselman, 2005;Walsh, 2001;Walsh & Vito, 2004;Weisburd, Mastrofski, Willis, & Greenspan, 2006) provides ample food for thought regarding the positive and negative outcomes that the Compstat model has had on police administration. Yet another set of scholars (Braga, 2001;Chilvers & Weatherburn, 2004;Conklin, 2003;Eck & Maguire, 2000;Greene, 1999;Joanes, 1999;Kelling & Bratton, 1998;Kelling & Sousa, 2001;Levitt, 1997Levitt, , 2004Mazerolle, Rombouts, & McBroom, 2007;Rosenfeld, Fornango, & Baumer, 2005;Sousa, 2003;Unter, 2007;Weisberg, 2005) have sought to document the impact that the Compstat model has had on jurisdictional crime rates and various forms of targeted social disorder.…”
Section: Scholarly Research On the Compstat Modelmentioning
confidence: 99%